Analytical Study of Shape of Tall Building Subjected to Wind Load for Steel Frame Structures - Rakesh Kumar, Shital A. Patage, Abhay B. Shelar, Supriya B. Shinde (Mathematical Statistician and Engineering Applications, 2022)
Shapes like rectangles, circles, hexagons, and pentagons at different heights are used to assess the stability of skyscrapers. Using a wind rise diagram and the STADD pro for Steel Frames design program, the experimental investigation will examine the impact of a building's shape on wind load. An FEM study is used as the foundation for the load calculations. Consequently, several research and investigations have been conducted to lessen the possibility of such an excitation and to strengthen tall buildings' resilience to the consequences of wind loads and earthquake loads. The architectural design of tall buildings relies heavily on the early integration of aerodynamic form and structural system choices in order to lessen the building's sensitivity to wind excitations.